Caries disease in childhood cancer patients: a literature review - Julia Pianezzer Miquelão; Julia Funez Barros; Bruna Cristina Longo (RGO: Revista Gaúcha de Odontologia)
ABSTRACT This study aims to present the prevalence of dental caries in childhood cancer patients, emphasizing the effects of antineoplastic therapy. To carry out the study, a search strategy was adopted that covered books from 2017 to 2022 and articles available in databases, published between 1997 and 2021, in English and Portuguese. In recent years, there has been an increase in the incidence of malignant neoplasms in pediatric patients. The most common are leukemias, lymphomas, and tumors of the central and sympathetic nervous systems. The treatment of these diseases is antineoplastic therapy, which aims to combat cancer cells. However, it can cause unwanted effects such as systemic, craniofacial, and dental changes. The most common oral manifestations are caries, microdontia, hypodontia, root changes and taurodontism. The relationship between tooth decay and childhood cancer is still not well understood, as factors such as diet and oral hygiene can play a confounding role in the development of tooth decay. Antineoplastic therapy increases the patient’s risk of developing caries disease, however, it has not yet been proven to be a disease-modifying factor, so additional studies must be carried out.